1996
DOI: 10.1104/pp.112.4.1573
|View full text |Cite
|
Sign up to set email alerts
|

Driving Forces for Bicarbonate Transport in the Cyanobacterium Synechococcus R-2 (PCC 7942)

Abstract: Air-grown Synechococcus R-2 (PCC 7942) cultures grown in BC-11 medium are very alkaline (outside pH is 10.0) and use HC0,-as their inorganic carbon source. The cells showed a dependente on Na+ for photosynthesis, but low Na+ conditions (1 mo1 m-3) were sufficient to support saturating photosynthesis. The intracellular dissolved inorganic carbon in the light was greater than 20 mo1 m-3 in both low-Na+ conditions and in BC-11 medium containing the usual [Na+] (24 mo1 m-,, designated high-Na+ conditions). l h e e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…5). These data are consistent with the suggestion that SbtA is a component of a Na ϩ /HCO 3 Ϫ symporter that drives the HCO 3 Ϫ transport secondary to a primary Na ϩ pump (7,9,10 (21) concluded that the Na ϩ flux was not sufficient to support the rate of photosynthesis (thought to be supported solely by HCO 3 Ϫ transport). However, photosynthesis in both Synechocystis 6803 and Synechococcus 7942 is largely supported by CO 2 uptake, even at high external pH.…”
Section: Fig 6 Phylogenetic Trees Of Sbta (A) and Ntpj (B)supporting
confidence: 80%
See 1 more Smart Citation
“…5). These data are consistent with the suggestion that SbtA is a component of a Na ϩ /HCO 3 Ϫ symporter that drives the HCO 3 Ϫ transport secondary to a primary Na ϩ pump (7,9,10 (21) concluded that the Na ϩ flux was not sufficient to support the rate of photosynthesis (thought to be supported solely by HCO 3 Ϫ transport). However, photosynthesis in both Synechocystis 6803 and Synechococcus 7942 is largely supported by CO 2 uptake, even at high external pH.…”
Section: Fig 6 Phylogenetic Trees Of Sbta (A) and Ntpj (B)supporting
confidence: 80%
“…SbtA-mediated HCO 3 Ϫ transport activity was highest at pH 9.0 and lowest at pH 7.0, whereas the ⌬H ϩ in cyanobacteria declines with rising pH. At alkaline pH such as 9.0, ⌬H ϩ would not suffice to drive HCO 3 Ϫ uptake (8,21). We cannot dismiss the possibility that Na ϩ binds to the HCO 3 Ϫ carrier and alters its kinetic parameters (7,10).…”
Section: Fig 6 Phylogenetic Trees Of Sbta (A) and Ntpj (B)mentioning
confidence: 79%
“…Additionally, disruption of the nha2 gene resulted in a lowNa ϩ requirement that was essential at alkaline pH. A threshold concentration of Na ϩ in growth media is essential for cyanobacteria to establish the necessary Na ϩ gradient across their membranes in order to take up nutrients (34,49,51,61) and to survive under alkaline conditions (3,13). Although the Nha2 protein is unable to complement the salt-sensitive phenotype of TO114 cells and despite the low transcript levels of the nha2 gene, our results suggest that Nha2 is involved in low-Na ϩ -dependent pH regulation of cyanobacterial cells under alkaline conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Prochlorococcus; Badger & Price 2003). Bicarbonate accumulation in the cytoplasm is thought to have an ATP : HCO K 3 or NADH : CO 2 cost ratio of 1 (but see Ritchie et al 1996). This ATP demand for CCM operation can be supplied directly by thylakoid pathways described in §5 (figure 6), including the pseudocyclic pathway (Mehler; Miller et al 1988;Sü ltemeyer et al 1993).…”
Section: Nutrientsmentioning
confidence: 99%